Traditions in architecture: Africa, America, Asia, and Oceania - Crouch, Dora P.; Johnson, June Gwendolyn (New York : Oxford : Oxford University Press, 2001)
An introduction to the architectural achievements of diverse cultures outside the Euro-American tradition. Arranged thematically, it focuses on the basic needs common to all communities, discusses architectural solutions and compares geographically separate buildings and construction traditions.
Section I Multiplicity and continuity in tradition: form and content; transfer of traditional architectural knowledge. Section II Water, shelter, and food - practial solutions: survival - water, shelter, and food; climate and biology; materials, methods, and architectural form. Section III Purposes of traditional architecture: spaces for daily life; religious architecture - a continuum of meaning; expression of power. Section IV Planning and design: land use; building types and uses; organization and structures. Section V Cultural types: vernacular and monumental combinations; symbolism and ornamentation; architecture and social relations; theories of architecture; architectural decision-making; the economics of building.
Includes bibliographical references (pages 391-418) and index.
Keywords: Vernacular architecture -- Research -- Africa; Vernacular architecture -- Asia; Vernacular architecture -- Oceania; Vernacular architecture -- Research -- America